Kajian Tematik: Sifat Berkeluh Kesah Perspektif Qur’ani - Harahap, Kifayatun Nisa Nautir; Enghariano, Desri Ari (Jurnal El-Thawalib, 2024)
This research examines complaining in the view of the Qur'an. This type of research is library research. This research is a normative research with a qualitative approach. The primary data source is the book of Tafsir which has an adabi ijtima'i pattern with the title Tafsir al-Maraghi while the secondary data is journal articles, books that are relevant to the subject matter above. The data analysis technique that the writer uses is descriptive-analytic. The results of this study are narratives of lamentation in the Koran, namely, in the words hazana (grief), khauf (worry and fear), syahiqun (inhale with moaning), lau (if only), and yaiasu (give up). Factors that cause humans to complain are feeling frustrated and weak when tested, when tests come they feel the most suffering, and when heavy tests and calamities befall them and the solution to overcoming complaints in the Qur'an is to strengthen faith, patience and piety to Allah SWT.